Perlakuan Dosis Pupuk Hayati Mikoriza dan Macam Varietas Terhadap Pertumbuhan Dan Hasil Tanaman Kacang Hijau (Phaseolus radiatus L.) - Kholik, Dian Abdul; Kustiani, Edy; Saptorini, Saptorini; Hadiyanti, Nugraheni (Jurnal Ilmiah Pertanian Nasional, 2023)
Mung bean (Phaseolus radiatus L.) is a functional food commodity used for feed ingredients and industry. The use of mycorrhizal fungi in different varieties will have other effects. This study aimed to determine the interaction of the dose of mycorrhizal biofertilizer and plant varieties on the growth and yield of mung bean. The research emphasized the interaction effect between doses of mycorrhizal biofertilizers on the development and yield of several varieties of mung beans. The experiment took place in the experimental garden of the Faculty of Agriculture, Kadiri University, Kediri, East Java, from December 2021 to March 2022. The experimental design used a 2-factor Randomized Block Design (RBD) with three replications. The first factor was the dosage of mycorrhizal biofertilizers: 0 gr/plot (U0), 150 gr/plot (U1), and 300 gr/plot (U2). The second factor was the plant varieties, consisting of Vima-1 (V1), Vima-2 (V2), and Vima-3 (V3). Data analysis used analysis of variance (ANOVA) and further tested by Tukey’s Honestly Significant Difference (HSD) at a 5% level. Based on the experiments, there was no interaction between the mycorrhizal doses and the different varieties on the variable of plant height, number of leaves, stem diameter, pod length, and plant fresh weight. The combination of mycorrhizal doses and variety showed a significant effect on the number of pods, pod weight, number of seeds planted, weight of seeds planted, weight of 100 seeds per plant, root length, and number of secondary roots, dry weight of plants, the fresh and dry weight of root. The combination of the mycorrhizal dose of 300 gr/plot and the Vima-2 (U2V2) variety gave better mung bean yields than the other treatments. Kacang hijau (Phaseolus radiatus L.) sebagai komoditas pangan fungsional, dimanfaatkan juga untuk bahan pakan dan industri. Pemanfaatan jamur mikoriza pada varietas tanaman kacang hijau yang berbeda memberikan pengaruh yang berbeda pula. Penelitian bertujuan untuk mempelajari pengaruh interaksi antara dosis pupuk hayati mikoriza terhadap pertumbuhan dan hasil beberapa varietas kacang hijau. Percobaan bertempat di kebun percobaan Fakultas Pertanian Universitas Kadiri Kediri, Jawa Timur pada bulan Desember 2021 sampai Maret 2022. Rancangan percobaan menggunakan Rancangan Acak Kelompok (RAK) 2 faktor dengan tiga kali ulangan. Faktor pertama adalah dosis pupuk hayati mikoriza: 0 gr/plot (U0), 150 gr/plot (U1), dan 300 gr/plot (U2). Faktor kedua adalah macam varietas, terdiri atas: Vima-1 (V1), Vima-2 (V2), dan Vima-3 (V3). Analisis data menggunakan analisis ragam (ANOVA), dan uji lanjut Beda Nyata Jujur (BNJ) taraf 5% apabila hasil berbeda nyata. Berdasarkan percobaan, tidak terjadi interaksi antara perlakuan dosis mikoriza dan macam varietas terhadap variabel tinggi tanaman, jumlah daun, diameter batang, panjang polong, dan berat basah tanaman. Kombinasi perlakuan dosis mikoriza dan macam varietas menunjukkan pengaruh nyata terhadap jumlah polong, berat polong, jumlah biji pertanaman, berat biji pertanaman, berat 100 biji per tanaman, panjang akar dan jumlah akar sekunder, berat kering tanaman, berat basah akar, dan berat kering akar. Kombinasi perlakuan dosis mikoriza 300 gr/plot dan varietas Vima2 (U2V2) memberikan hasil kacang hijau lebih baik daripada perlakuan lainnya.